GROWTH OF CRYSTALS OF PRIMARY ALUMINIUM WITH ROSETTE MORPHOLOGY AT CASTING OF SILUMINS - E. I. Marukovich (Litʹë i Metallurgiâ, 2011)
The work is devoted to actual theme of alloy solidifi – investigation of infl of overlapping of thermal and concentration fi of neighboring crystals to forming of non- dendrite structures. Experimental research of microstructure of Al-Si alloy for wide range of silicon concentration is conducted, and corresponding numerical simulation develop too. The conclusion about different schemes of forming of rosette structures is adopted.